Imaging of post-embryonic stage model organisms at high resolution using multi-orientation optoacoustic mesoscopy - Omar, Murad; Rebling, Johannes; Wicker, Kai; Schmitt-Manderbach, Tobias; Schwarz, Mathias; Gateau, Jerome; Lopez-Schier, Hernan; Mappes, Timo; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
Model organisms such as zebrafish play an important role for developmental biologists and experimental geneticists. Still, as they grow into their post-embryonic stage of development it becomes more and more difficult to image them because of high light scattering inside biological tissue. Optoacoustic mesoscopy based on spherically focused, high frequency, ultrasound detectors offers an alternative, where it relies on the focusing capabilities of the ultrasound detectors in generating the image rather than on the focusing of light. Nonetheless, because of the limited numerical aperture the resolution is not isotropic, and many structures, especially elongated ones, such as blood vessels and other organs, are either invisible, or not clearly identifiable on the final image. Herein, based on high frequency ultrasound detectors at 100 MHz and 50 MHz we introduce multi orientation (view) optoacoustic mesoscopy. We collect a rich amount of signals from multiple directions and combine them using a weighted sum in the Fourier domain and a Wiener deconvolution into a single high resolution three-dimensional image. The new system achieves isotropic resolutions on the order of 10 μm in-plane, 40 μm axially, and SNR enhancement of 15 dB compared to the single orientation case. To showcase the system we imaged a juvenile zebrafish ex vivo, which is too large to image using optical microscopic techniques, the reconstructed images show unprecedented performance in terms of SNR, resolution, and clarity of the observed structures. Using the system we see the inner organs of the zebrafish, the pigmentation, and the vessels with unprecedented clarity.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Beam-forming; Mesoscopy; Microscopy; Multiview; Optoacoustics